VISUALISASI ANALISIS SENTIMEN SIBERBULLYING PADA POST INSTAGRAM MENGGUNAKAN ORANGE DATA MINING - Hindun Nur Azizah (The Indonesian Journal of Computer Science Research, 2023)
Instagram is a social media that is often used in the digital era like today. Many users from various walks of life use Instagram. But of the many benefits of Instagram, the negative impact of social media is undeniable, cyberbullying is a negative impact that always lurks whenever and wherever. The dangers of cyberbullying can be troubling to many parties. Cyberbullying on Instagram often occurs in the comments column, therefore this study was conducted to analyze the sentiment of cyberbullying in Instagram comments. Sentiment analysis is a branch of science from text mining that is used to extract and process data in the form of text. To find out the results of the art, this study uses webharvy as a tool to collect data, and orange data mining as a tool to analyze. This research method is qualitative because Instagram comments are research material